Early exposure to animals and childhood body mass index percentile and percentage fat mass. Issue 1 (31st December 2022) - Ferguson, Pamela L.; Commodore, Sarah; Neelon, Brian; Cobbs, JacKetta; Sciscione, Anthony C.; Grobman, William A.; Newman, Roger B.; Tita, Alan T.; Nageotte, Michael P.; Palomares, Kristy; Skupski, Daniel W.; Vena, John E.; et al.
ABSTRACT: Introduction: A few studies have identified childhood animal exposure as associated with adiposity, but results are inconsistent and differ in timing. Methods: We conducted an observational cohort study of children ages 4–8 in the Environmental Influences on Child Health Outcomes [ECHO] study. The main exposure was having a dog in the home and/or regular contact with farm animals during the first year of life. Outcomes of interest were child BMI percentile (adjusted for gender and age) categorized as normal/underweight (<85 th percentile), overweight (85 th to <95 th ), and obese (≥95 th ), and percent fat mass (continuous). Associations were analyzed using multinomial logistic regression and multivariable linear regression, respectively, with and without multiple imputation. Results: First-year animal exposure occurred in 245 of 770 (31.8%) children. Children with early animal exposure had 0.53 (95% CI: 0.28, 0.997) times the odds of being in the obese BMI category compared to those exposed to animals after controlling for covariates: maternal pre-pregnancy BMI, race/ethnicity, reported child activity level, receiving food assistance, age child began daycare (<1 year vs 1+), exclusively breastfed x6 months, and NICU admission (n = 721). Children with early animal exposure had, on average, 1.5% (95% CI: −3.0, −0.1) less fat mass than exposed children after adjustment for maternal BMI, race/ethnicity, activity, food assistance, breastfeeding, and maternal education (n = 548). Multiple imputation did not alter either result. Conclusion: These results provide evidence that exposure to dogs or farm animals in the first year of life is associated with lower odds of obesity and lower percent fat mass in childhood.